Assessment of Clinical, Respiratory and Metabolic Parameters in Neonatal Calves in Different Courses of Aspiration Pneumonia - Gülersoy, Erdem; Balıkçı, Canberk; Şahan, Adem; Günal, İsmail (The Iraqi Journal of Veterinary Medicine, 2023)
Iatrogenic aspiration pneumonia (AP), often caused by incorrect drenching and ‎feeding with inappropriate bottles, is a frequent condition that can lead to sudden death ‎depending on the amount of aspirated fluid. The evaluation of clinical scores‎ and blood ‎gas analytes may provide valuable insights into the complications that may arise due to AP in later ‎stages. In this study, the AP Group consisted of ‎23 Holstein breed calves aged 1-14 days, ‎which developed clinical signs such as cough, nasal and/or ocular discharge, and respiratory ‎distress after forced feeding with inappropriate bottles. The Control Group consisted of 11 healthy calves with similar characteristics. Clinical examinations, Calf ‎Health Score (CHS) evaluations, and venous blood gas analysis were performed. Based on anamnesis, calves with AP were classified as either Acute or Chronic AP. In clinical ‎examination, heart and respiratory rates were higher in the Acute AP Group compared to the ‎other groups (P<0.001). Total CHS was higher in the AP Group than that in the Control ‎Group (P<0.001). The pH, sO2, Cl and Hb levels of the AP Group were lower, and K and ‎lactate levels were higher compared to the Control Group (P<0.031). Among all groups, ‎the pCO2 levels were highest in the Acute AP Group (P<0.001). The Na level of the Chronic ‎AP Group was lower than that of the Control Group (P<0.05). The hematocrit level was ‎lowest in the Chronic AP Group (P<0.016). These findings suggest that venous blood samples can be effectively used to classify the course of AP ‎in neonatal calves; significant alterations in venous blood gas, electrolyte levels, and CHS can ‎be observed in affected animals; sO2 and pCO2 levels are particularly important in ‎distinguishing between acute and chronic cases of AP; and clinical and laboratory findings may ‎be similar to those observed in healthy animals in chronic cases depending on the body’s ability ‎to compensate or tolerate the disease.